Aplicación de analítica digital, marketing digital y nuevas tecnologías en empresas peruanas - Calderon Portocarrero, Kevin Ray (2022)
A systems engineer, graduated from the University of Lima, must be able to apply information technology knowledge, research capacity and analytical capacity to design creative solutions to the challenges faced by the company for which he works; ensuring at all times to observe ethical principles and social responsibility. Likewise, they must have skills, among which effective communication, conscious leadership, among others, that allow them to effectively manage complex projects. I began my professional development, working in digital analytics and digital marketing consultancy with different companies in the banking and insurance, retail, education, and tourism sectors, among others, where I gained both technical and project management and leadership experience. Among the main achievements that I highlight in this experience, is the development of technical, business and management knowledge and skills that allowed me to lead digital analytics and digital marketing projects. Secondly, I managed to pursue a career line in the consultancy, growing from a professional intern to a senior consultant with the role of leader of the digital analytics chapter, thanks to having demonstrated good performance in projects. I am currently working in a company in the retail sector, using my analytical skills and technological knowledge to generate value with data for the business objectives presented by different projects in which I participate. My main achievement in this experience is meeting the business objectives per project and leading the relationship with the main stakeholders with whom I work. I believe that one of the most important aspects that every systems engineer must keep in mind is not to stop learning. We live in a world, where constant changes occur in a short time, so we must always be prepared to adapt to new technologies, processes and changes that may occur in society.